Becoming Global Citizens in Maternal Child Nursing. Issue 3 (May 2020) - Callister, Lynn Clark
Abstract : This year has been designated as the World Health Organization (WHO) International Year of the Nurse and Midwife in honor of the bicentenary celebration of Florence Nightingale. Nurses and midwives are the largest group of health care workers globally and as such are essential stakeholders in promoting world health. Our global health and nursing expert, Dr. Callister, presents implications for maternal-child nurses and how we can all become global citizens.